THE IMPACT OF COVID-19 ON MATHEMATICS EDUCATION STUDENT’S RELATIONSHIPS BETWEEN PEERS, LECTURERS AND PARENTS DURING ONLINE LEARNING - Mohd Rijal Ilias; Amir Farhat Mohd Fauzi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Global education systems have experienced an abrupt disruption in traditional classroom instruction due to the coronavirus pandemic, which compelled all schools to close in March 2020 and introduced home-based distance learning. Consequently, families, schools, and students have had to collaborate more closely. The shift to online learning can impact student relationships. Maintaining open communication with peers, seeking virtual interactions with lecturers, and involving parents in the learning process can foster a supportive environment. Thus, this study is to determine the impact of COVID-19 on student’s relationships between peers, lecturers, and parents during online learning. Questionnaires were distributed to Education Mathematics’ students. Total respondents are 82 students. Dependent variable is online learning and three independent variables are student’s relationship with classmates, student’s relationship with lecturers and student’s relationship with family. Data was analysed by using SPSS statistical tool. ANOVA test used to determine significant factors towards values in mathematics and path analysis testing the established hypotheses. The result indicated all three factors shows a significant factor. It means that student’s relationship with classmates/peers, lecturers/faculty, and family play an important role during online class. Recommendations include utilizing online platforms for group activities and addressing concerns promptly to ensure a positive learning experience.